Standard and Z2-Regge theory in two dimensions - Bittner, Elmar; Hauke, Alf; Holm, Christian; Janke, Wolfhard; Markum, Harald; Riedler, Jürgen (Nuclear physics. Proceedings supplements, 1998)
We qualitatively compare two versions of quantum Regge calculus by means of Monte Carlo simulations. In Standard Regge Calculus the quadratic link lengths of the triangulation vary continuously, whereas in the Z2-Regge Model they are restricted to two possible values. The goal is to determine whether the computationally more easily accessible Z2 model retains the characteristics of standard Regge theory.
Elektronische Reproduktion der Druck-Ausgabe
Available online 14 August 2000
Im Titel ist die Zahl "2" tiefgestellt
Gesehen am 18.10.2022